Music a very short introduction - Cook, Nicholas 1950- (Very short introductions, 2021)
Nicholas Cook explores the nature of music, how we think about it, its social and cultural dimensions, and its history. He discusses the many musical traditions across the world and the interactions between them. He also considers performance, how composers create music, and the position of music in today's globalized society